Method for manufacturing a thermoelectric conversion element and a method for manufacturing a thermoelectric conversion module using the same

The method of sintering thermoelectric conversion material powder with Ti-Al alloy foil addresses the challenge of crack formation and densification, ensuring reliable electrical performance by suppressing Al-Sb formation and maintaining material integrity.

JP7604969B2Active Publication Date: 2024-12-24PROTERIAL LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021047269
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-26
Filing Date
2021-03-22
Publication Date
2024-12-24
Estimated Expiration
2041-03-22

AI Technical Summary

Technical Problem

Existing methods for manufacturing thermoelectric conversion elements face challenges in controlling sintering to densify the thermoelectric conversion material powder while preventing cracks and diffusion at the joint, particularly on the high temperature side, which can lead to electrical performance deterioration.

Method used

A method involving the sintering of thermoelectric conversion material powder with an alloy foil containing Ti and Al, where the alloy foil has a specific crystal orientation difference and Al content, forming a diffusion prevention layer that suppresses crack formation and densifies the material.

Benefits of technology

The method effectively prevents crack formation and densifies the thermoelectric conversion material, maintaining electrical performance by minimizing the formation of brittle Al-Sb compounds and ensuring reliable bonding.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007604969000002
    Figure 0007604969000002
  • Figure 0007604969000003
    Figure 0007604969000003
  • Figure 0007604969000004
    Figure 0007604969000004
Patent Text Reader

Abstract

To solve a problem in which a crack and the like occur in a diffusion prevention layer at a joint, and it is difficult to make the diffusion prevention layer dense at the same time as the powder of a thermoelectric conversion material.SOLUTION: A manufacturing method of a thermoelectric conversion element includes a step of sintering a thermoelectric conversion material powder containing Sb in contact with an alloy foil containing Ti and Al to obtain a thermoelectric conversion material having a diffusion prevention layer, and in the alloy foil containing Ti and Al, in a cross-section observation method that can determine an orientation difference of a crystal, when an area of 5000 μm2 or more is observed, the number of crystal grains defined by the grain boundaries with an orientation difference of 10 degrees or more is 1.0 or less / 5000 μm2.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for manufacturing a thermoelectric conversion element for converting heat into electricity, and a method for manufacturing a thermoelectric conversion module using the same. [Background technology]

[0002] For example, in order to effectively utilize heat from high-temperature areas such as factory exhaust heat, thermoelectric conversion modules that convert heat into electricity are being studied. Thermoelectric conversion modules consist of many thermoelectric conversion elements. Thermoelectric conversion elements generate electromotive force according to the temperature difference between the high-temperature side and the low-temperature side, and by connecting N-type and P-type thermoelectric conversion elements in series and arranging one side as the high-temperature side and the other side as the low-temperature side, heat can be converted into electricity.

[0003] In recent years, Sb-based thermoelectric conversion materials that have a skutterudite structure and contain Sb have been attracting attention as thermoelectric conversion materials with high electrical properties (figure of merit ZT). If this skutterudite-based thermoelectric conversion element is used, it can efficiently convert heat into electricity, for example, when the high-temperature part is about 300°C to 500°C.

[0004] When such a thermoelectric conversion element is used as a thermoelectric conversion module, electrodes are joined to the high-temperature side and the low-temperature side, respectively. However, particularly on the high-temperature side, solid-phase diffusion may progress between the electrodes and the thermoelectric conversion element, causing a risk of partial deterioration of the thermoelectric conversion element. In addition, particularly on the high-temperature side, a thermal cycle may occur, causing a risk of cracks or the like in the diffusion layer at the joint. Such a state may cause an increase in electrical resistance, etc., and result in a decrease in electrical performance.

[0005] In response to this, Patent Document 1 proposes a method of filling the end of a thermoelectric element alloy powder with Ti powder or a mixed powder of Ti powder and Al powder and simultaneously sintering it in order to suppress diffusion between an Sb-based skutterudite thermoelectric element and an electrode material. Patent Document 2 also discloses a thermoelectric conversion element that is made of a sintered body including a thermoelectric conversion material made of an alloy containing Sb and a diffusion prevention layer made of an alloy containing Ti and Al, laminated on the thermoelectric conversion material, in which the neck part of the sintered body constituting the diffusion prevention layer is Ti-Al alloyed, and the Al concentration in each part of the sintered body is 50 at% or less. As a result, it is possible to provide a highly reliable thermoelectric conversion element that can maintain electrical characteristics by suppressing the Al-enriched part (Al-Sb) that is mainly made of Al and Sb and is more brittle than the surrounding area, and reducing cracks starting from the part. Here, the notation Ti-Al alloy means that it is an alloy that contains the element Ti and the element Al as main elements (highest elements in terms of content). [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2011-249442 A [Patent Document 2] JP 2019-169534 A Summary of the Invention [Problem to be solved by the invention]

[0007] The diffusion prevention layers described in Patent Documents 1 and 2 both use powder and are sintered simultaneously with the thermoelectric conversion material powder. In this case, the difficulty of controlling the sintering to densify simultaneously with the thermoelectric conversion material powder was an issue.

[0008] An object of the present invention is to solve the problem of cracks and the like occurring in the diffusion layer at the joint, as described in Patent Documents 1 and 2, and also to solve the problem of densification due to simultaneous sintering with powder of thermoelectric conversion material. [Means for solving the problem]

[0009] The method for producing a thermoelectric conversion element of the present invention includes a step of sintering a powder of the thermoelectric conversion material containing Sb and an alloy foil containing Ti and Al in contact with each other to obtain a thermoelectric conversion material having a diffusion prevention layer, and the alloy foil containing Ti and Al is sintered in a state in which the difference in crystal orientation can be determined by observing a cross section of the alloy foil having a thickness of 5000 μm or less. 2 When observing an area of ​​this size, the number of crystal grains defined by grain boundaries with a misorientation of 10 degrees or more is 1.0 or less per 5000 μm 2 It is characterized in that:

[0010] Furthermore, the alloy foil containing Ti and Al preferably has an Al content of 8 mass % or more and 36 mass % or less and has a Ti3Al compound.

[0011] Furthermore, the method for producing a thermoelectric conversion module of the present invention preferably includes a step of bonding the thermoelectric conversion element obtained by the above-mentioned method for producing a thermoelectric conversion element to an electrode via the diffusion prevention layer. Effect of the Invention

[0012] According to the present invention, it is possible to provide a method for manufacturing a thermoelectric conversion element that can suppress the occurrence of cracks and the like in the diffusion layer at the joint and can simultaneously densify the powder of the thermoelectric conversion material. [Brief description of the drawings]

[0013] [Figure 1] FIG. 1 is a perspective view showing an overall structure of a thermoelectric conversion module. [Diagram 2] FIG. 2 is an enlarged cross-sectional view of a thermoelectric conversion module. [Diagram 3] FIG. 2 shows the results of X-ray diffraction of Ti-Al foil. [Figure 4] Cross-sectional SEM image of the bonding interface between Ti-Al foil and a thermoelectric conversion element containing Sb. [Diagram 5] Figure 4 shows the EDX line analysis results for the vicinity of the bonded interface. [Figure 6] Manufacturing process flow diagram for thermoelectric conversion material with Ti-Al foil. [Figure 7] SEM-EDX analysis results of Example 1. [Figure 8] 1 shows the results of SEM-EDX analysis of Example 1, which was subjected to a high-temperature storage test. [Figure 9] SEM-EDX analysis results of Example 2. [Figure 10] SEM-EDX analysis results of Example 3. [Figure 11] SEM-EDX analysis results of Example 4. [Figure 12] 13 shows the results of SEM-EDX analysis of Example 5, which was subjected to a high-temperature storage test. [Figure 13] SEM observation results of Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. FIG. 1 is a perspective view showing the overall structure of a thermoelectric conversion module 10 of this embodiment. The thermoelectric conversion module 10 is composed of P-type thermoelectric conversion elements 21, N-type thermoelectric conversion elements 22, electrodes 30, and a ceramic wiring substrate 40. Adjacent P-type thermoelectric conversion elements 21 and N-type thermoelectric conversion elements 22 are arranged in a staggered pattern and are electrically connected in series via the electrodes 30 and the ceramic wiring substrate 40. The N-type thermoelectric conversion elements 22 and the P-type thermoelectric conversion elements are made of a thermoelectric conversion material containing Sb, and it is particularly preferable that they have a skutterudite structure. For example, the P-type thermoelectric conversion element 21 is made of Ce. x Fe y Mn 4-y Sb 12 , the N-type thermoelectric conversion element 22 is Yb x Co4Sb 12is preferable. In the case of a skutterudite structure containing Sb, the above composition may contain other trace elements. A thermoelectric conversion material with a skutterudite structure has high power generation performance in a temperature range of 300 to 500°C, and it is possible to obtain high output by obtaining a large temperature difference. Therefore, it is preferable that the thermoelectric conversion material containing Sb is identified by XRD and is a single phase of the skutterudite structure. A thermoelectric conversion material containing Sb means that Sb is contained in a state where it is easily reacted, such as a composition containing more Sb than other elements, or a composition with other elements that are more stable than Sb.

[0015] The electrodes 30 may be made of any material that can conduct electricity even in a temperature range of 300 to 500° C. Furthermore, any material that has a thermal expansion coefficient close to that of the P-type thermoelectric conversion elements 21 and the N-type thermoelectric conversion elements 22 may be used, and may have a structure made of a single layer of pure metal or alloy, or multiple layers of pure metal or alloy. In particular, in the case of a thermoelectric conversion material containing Sb, it is preferable that the material is a composite material in which thermal expansion is adjusted by mixing Cu or Cu and Mo (composite in a granular form, layered form, etc.).

[0016] The ceramic wiring board 40 only needs to have insulating properties, and it is preferable to use a ceramic material such as alumina, aluminum nitride, or silicon nitride, since it can be used in a wide temperature range from low to high temperatures.

[0017] 2 shows an enlarged cross-sectional view of a portion of the thermoelectric conversion module. A first conductive member 41 and a second conductive member 42 are formed on both sides of a ceramic wiring substrate 40. The first conductive member 41 and the second conductive member 42 may be made of a material such as Cu, similar to the electrode 30. The first conductive member 41 may be provided with a metal film (not shown) such as Ni for the purpose of improving the bondability to the bonding layer 60.

[0018] The bonding layer 60 may be made of solder, brazing material, or a metal nanoparticle sintered layer. When a sintered layer using a metal nanoparticle paste is formed as the bonding layer 60, it is desirable because it does not melt even when the thermoelectric conversion module operates at a temperature higher than the bonding temperature, and is highly reliable. When the first conductive member 41 is Cu, it is more preferable that the bonding layer 60 is a sintered layer of Cu. That is, a sintered layer of Cu is formed by using a metal nanoparticle paste containing Cu.

[0019] The metal layer 51 has the role of facilitating bonding between the ceramic wiring substrate and the P-type thermoelectric conversion element 21 and the N-type thermoelectric conversion element 22 via the bonding layer 60. Various metal layers 51 can be selected in consideration of the bonding with the bonding layer 60, and Ni is particularly preferable when the bonding layer 60 is a sintered layer of Cu. As is clear from the equilibrium phase diagram, Cu and Ni form a complete solid solution. Therefore, necks are easily formed, enabling strong bonding.

[0020] A method for forming the metal layer 51 may be appropriately selected depending on the presence or absence of the diffusion prevention layer 50. For example, the diffusion prevention layer 50 may be formed at least on one side of the electrode 30. In other words, the diffusion prevention layer 50 on the ceramic wiring substrate side may not be formed, in which case the metal layer 51 may be formed on one surface of the P-type thermoelectric conversion element 21 and the N-type thermoelectric conversion element 22. When forming the metal layer 51 on the surface of the P-type thermoelectric conversion element 21 and the N-type thermoelectric conversion element 22, a plating method or the like may be applied. When forming the diffusion prevention layer 50, Ni may be bonded as the metal layer 51 at the same time as bonding the thermoelectric conversion material and the diffusion prevention layer 50.

[0021] The diffusion prevention layer 50 is formed of Ti-Al foil manufactured from a cast alloy, and is preferably composed of crystal grains with grain boundaries having an orientation difference of less than 10 degrees in a cross-sectional observation range of 100 μm × 50 μm. More preferably, it is composed of crystal grains with an orientation difference of 2 degrees or less in the crystal grain boundaries. Here, when one or more crystal grains are present in the metal structure, they are collectively referred to as a crystal grain group. Each crystal grain in the crystal grain group can be identified by a color map using EBSD (Electron Backscatter Diffraction). In the case of a crystal grain group composed of crystal grains with an orientation difference of 10 degrees or more, it can also be identified by a BSE image (Back Scattered Electron). In the evaluation using EBSD, by specifying a reference orientation difference, if crystal grains exist on both sides of a crystal grain boundary at an angle equal to or greater than the specified orientation difference, they are judged as individual crystal grains. In other words, when there are crystal grains on both sides of a crystal grain boundary with an orientation difference less than the reference difference, they are judged as one crystal grain rather than as individual crystal grains. In addition, the foil may be expressed as a plate, a flake, a thin plate, a film, or the like, and there are no limitations on the thickness or shape, so long as it can function as a diffusion prevention layer during use as a thermoelectric conversion element.

[0022] The Ti-Al foil is preferably mechanically cut from a Ti-Al ingot using a wire saw or the like, and then adjusted to a specified thickness by lapping or the like. By using a Ti-Al foil composed of crystal grains with a grain boundary misorientation of less than 10 degrees, it is possible to suppress the thickness of the reaction layer 501 shown in Fig. 2 to 30 μm or less, and to prevent the generation of an Al-Sb compound phase that causes a decrease in reliability. The thickness of the reaction layer may be the average thickness calculated from cross-sectional observation using a SEM (Scanning Electron Microscope), etc.

[0023] It is preferable to prepare Ti-Al ingots by cold inclusive melting. A Ti-Al ingot can be obtained by melting and holding Al and Ti in a water-cooled copper crucible in a predetermined ratio, pouring the melt into a graphite mold installed in a melting furnace, and cooling it. The grain size and crystal quality of Ti-Al ingots vary depending on the effect of cooling. Therefore, it is preferable to melt Al and Ti by cold inclusive melting and cool them in a graphite mold for one hour. When cooling the ingots in this melting method, it is possible to replace the solidification process by taking into account the temperature gradient of the molten metal in the crucible, by pouring the molten metal from the low-temperature side, such as the bottom of the crucible, so as to draw it out and pour it into the mold, thereby preventing the occurrence of shrinkage cavities. It is also preferable to add HIP (Hot Isostatic Pressing) to the process, in which the solidified Ti-Al ingot is left in an inert atmosphere for a long time while being pressurized and heated, to remove shrinkage cavities.

[0024] In the case of Al-rich Ti-Al compounds (e.g., TiAl3), there is a concern that the reaction between Sb and Al in the thermoelectric conversion material promotes the formation of Al-Sb. Therefore, it is desirable to use Ti-rich Ti3Al as the composition of the Ti-Al foil. Therefore, it is preferable to prepare a Ti-Al ingot with a raw material ratio of Ti-19.5 mass%Al for cold inclusive melting. In addition, TiAl has a higher Al content than Ti3Al, but since it is an intermetallic compound with a high melting point, a Ti-Al ingot may be prepared with a ratio of Ti-34.2 mass%Al. Although these are all aimed at the stoichiometric ratio of compounds such as TiAl and Ti3Al, any composition ratio that can obtain these compounds will suffice. Therefore, the raw material ratio of Al to the whole is preferably 8 mass% or more and 36 mass% or less, and more preferably 19.5 mass% to 34.2 mass%.

[0025] Figure 3 shows the results of X-ray diffraction evaluation of the surface of Ti-Al foil. Ti-Al ingots were produced by cold inclusive melting with a melting feed ratio of Ti-19.5 mass% Al. Ti-Al ingots were cut to produce Ti-Al foil, and the results of X-ray diffraction analysis of its surface are shown. Diffraction peaks of Ti3Al were obtained. As shown in Figure 3, it is desirable to use Ti-Al foil where the peak intensity is greatest on the (201) plane of Ti3Al.

[0026] FIG. 4 shows an example of an electron microscope photograph of a cross section of a bonded N-type thermoelectric conversion element 22 when Ti-Al foil is used as the diffusion prevention layer 50. The electron microscope photograph is shown as a BSE image. Since the BSE image is affected by channeling contrast, the contrast of the image changes depending on the angle of incidence of the electrons with respect to the crystal orientation. Therefore, when the misorientation of the grain boundaries is 10 degrees or more, the grain boundaries are clearly observed. Since the Ti-Al foil is composed of grain boundaries with a misorientation of less than 10 degrees according to EBSD analysis, the difference in contrast is not clearly observed in the BSE image.

[0027] Grain boundaries with large misorientation contain many defects such as dislocations. As a result, the atomic arrangement is disordered, and the diffusion rate of atoms at the grain boundaries is much faster than the volume diffusion within the grains. In other words, when grain boundaries with large misorientation are contained in a Ti-Al alloy, the diffusion of Sb and other elements in the thermoelectric conversion material is more likely to occur, leading to a phase change. When Ti-Al undergoes a phase change, a reaction layer is formed at the bonding interface with the thermoelectric conversion material. The more the Ti-Al phase changes, the thicker the reaction layer becomes, and compound phases such as Al-Sb are generated, which can cause a decrease in reliability.

[0028] When Ti-Al foil is used as the diffusion prevention layer 50, it is possible to prevent the generation of Al-Sb and perform bonding. FIG. 5 shows an example of line analysis of the bonding interface between the diffusion prevention layer 50 using Ti-Al foil and the N-type thermoelectric conversion element 22 by EDX (Energy Dispersive x-ray Spectroscopy). It can be seen that there is no part where Al and Sb are relatively high, and no clear reaction layer such as the reaction layer 501 in FIG. 2 appears. That is, Al-Sb, which causes a decrease in reliability, is not confirmed. Although the reaction layer 501 is formed in some parts, the thickness of the reaction layer 501 is 30 μm or less, and Al-Sb, which causes a decrease in reliability, is not confirmed. It is sufficient for the reaction layer 501 to prevent the generation of Al-Sb, and there is no problem if it is a reaction layer formed of TiSb2, Ti-Co-Sb, or Ti-Al-Sb. By making the orientation difference of the crystal grain boundaries constituting the Ti-Al foil less than 10 degrees, it is possible to suppress the thickness of the reaction layer. Thus, it is expected that the Ti-Al foil may react with the adjacent thermoelectric conversion material powder or metal layer. The diffusion prevention layer only needs to have a function of preventing the diffusion of the reaction layer that would cause cracks during use as a thermoelectric conversion element, and for example, at least a Ti-Al layer may be provided between the adjacent thermoelectric conversion material powder or metal layer. Here, the length of the cracks does not need to interfere with the electrical properties of the thermoelectric conversion material. For example, the presence or absence of cracks may be determined by checking for cracks that are longer than 5 μm in a 20 μm square observation surface of an electron microscope photograph. Any point including the interface may be observed within the 20 μm square observation field, and it is preferable to check multiple points.

[0029] The Ti-Al foil in the region that does not contribute to the generation of the reaction layer 501 does not undergo a phase change before and after sintering with the thermoelectric conversion material. For example, when Ti-Al foil is manufactured with a melting raw material ratio of Ti-19.5 mass% Al, the main phase is Ti3Al, but the diffusion prevention layer 50 after sintering also maintains Ti3Al. Therefore, it is possible to obtain a diffusion prevention layer 50 with a high diffusion prevention effect.

[0030] 6 shows a manufacturing process flow for a thermoelectric conversion material with a Ti-Al foil diffusion prevention layer. As described above, the Ti-Al foil is manufactured by obtaining a Ti-Al ingot by pouring the molten metal into a graphite mold using a cold inclusive method or the like, and then cutting the ingot into a foil shape with a thickness of 50 μm to 300 μm using a wire saw or the like. The cut Ti-Al foil is polished and cleaned to obtain Ti-Al foil as the diffusion prevention layer 50.

[0031] Next, Ni foil, Ti-Al foil, and thermoelectric conversion material containing Sb are filled into the mold. When Ti-Al foil is formed on both sides of the thermoelectric conversion material, Ni foil, Ti-Al foil, thermoelectric conversion material containing Sb, Ti-Al foil, and Ni foil may be laminated from the bottom of the mold in this order. When Ti-Al foil is formed only on one side of the thermoelectric conversion material, for example, Ni foil, Ti-Al foil, and thermoelectric conversion material containing Sb may be laminated from the bottom of the mold in this order, and the thermoelectric conversion material containing Sb and Ni foil may be laminated interchangeably. A predetermined amount of thermoelectric conversion material containing Sb may be directly filled into the mold, or it may be molded in advance using a simple press or the like and laminated in the mold in the form of a green compact.

[0032] Next, the thermoelectric conversion material, Ti-Al foil, and Ni foil are pressure-sintered using a hot press, etc. For example, in the case of an N-type thermoelectric conversion material containing Sb, the sintering is performed by holding the material in an inert gas such as Ar at 700°C for 60 minutes and applying a pressure of 15 MPa to 68 MPa, thereby making it possible to bond the Ti-Al foil and the N-type thermoelectric conversion material containing Sb, and the Ti-Al foil and the Ni foil.

[0033] For example, the n-type thermoelectric material Yb x Co4Sb 12 In this case, even if a sintering aid alloy is included to improve sinterability, the same effect can be achieved by using the Ti-Al foil of this embodiment. That is, the thickness of the reaction layer formed at the interface between the thermoelectric conversion material and the Ti-Al foil can be suppressed to 30 μm or less, and the generation of Al-Sb can be prevented.

[0034] The Ti-Al foil and Ni foil are solid-state bonded, and a reaction layer such as Ti-Ni, Ni-Al, or Ti-Ni-Al may be formed in some places. Also, to improve the bondability of the Ti-Al foil and Ni foil, an Al layer with a low melting point (660°C) may be sandwiched between them. In this case, a reaction layer of Ti-Ni, Ni-Al, or Ti-Ni-Al is formed at the bond interface, just like in solid-state bonding.

[0035] It is possible to manufacture a thermoelectric conversion material with a diffusion prevention layer by the above method. The thermoelectric conversion material with a diffusion prevention layer is cut out by a wire saw or the like into the shapes of P-type thermoelectric conversion elements 21 and N-type thermoelectric conversion elements 22 shown in Fig. 1 and Fig. 2. After cutting, the material is placed on a ceramic wiring substrate 40 via a bonding material using a tool or the like, and electrodes are mounted and heated under pressure to obtain the thermoelectric conversion module 10 shown in Fig. 1. EXAMPLES

[0036] Example 1 A thermoelectric conversion element was fabricated by joining Ni foil, Ti-Al foil, and a thermoelectric conversion material containing Sb. The Ti-Al ingot, which is the raw material for the Ti-Al foil, was fabricated by the cold inclusive method. Pellet-shaped Ti and Al were mixed in a ratio of Ti-19.5 mass%Al and placed in a water-cooled copper crucible. After that, the inside of the melting furnace was heated to 6.6 × 10 -2 The furnace was evacuated to a vacuum of 100 Pa, and Ar gas was introduced. After the introduction of Ar gas, the alloy was melted by high-frequency melting, poured into a cylindrical graphite mold placed in the melting furnace, cooled, and one hour later, the Ti-Al alloy was removed from the graphite mold to obtain a Ti-Al ingot.

[0037] The obtained round-bar-shaped Ti-Al ingot was processed by wire electric discharge machining into a Ti-Al round bar of φ30 mm, and then a multi-wire saw was used to produce Ti-Al foil with a thickness of approximately 0.3 mm. The Ti-Al foil was processed to approximately 0.2 mm by lapping, and then washed with acetone to obtain the Ti-Al foil. The obtained Ti-Al foil was produced from the same lot as the Ti-Al foil evaluated in Figure 3. The Ti-Al foil used was one that did not contain crystal grains with an orientation difference of 10 degrees or more, as determined by cross-sectional EBSD analysis in an area of ​​100 μm x 50 μm.

[0038] The thermoelectric material is Yb 0.3 Co4Sb 12 The powder was compacted at a pressure of 21 MPa. Ni foil, Ti-Al foil, Yb 0.3 Co4Sb 12 The compact, Ti-Al foil, and Ni foil were layered in that order, and pressure sintered. Sintering was performed in an Ar atmosphere at 700°C for 60 minutes, with a pressure of 68 MPa. The resulting bonded body was embedded in resin, polished, and the cross section was observed to confirm the thickness of the reaction layer formed at the interface between the thermoelectric conversion material and the Ti-Al foil, and the presence or absence of Al-Sb formation.

[0039] FIG. 7 shows the SEM-EDX mapping analysis results of Example 1. The mapping analysis results are shown in gray scale, so they do not necessarily show the absolute abundance ratio of elements. 0.3 Co4Sb 12 No reaction layer exceeding 1 μm was observed in a field of view of approximately 30 μm along the interface, confirming that Al-Sb was not produced. Furthermore, no cracks exceeding 5 μm in length were observed in the observation field of 20 μm square indicated by the dashed line.

[0040] The thermoelectric conversion element of Example 1 was subjected to a high-temperature storage test in which it was held in an argon atmosphere at 600° C. for 100 hours. The results of the SEM-EDX mapping analysis after the high-temperature storage test are shown in FIG. 0.3 Co4Sb 12In a field of view of approximately 10 μm along the interface, no reaction layer exceeding 1 μm in size was observed, confirming that no Al-Sb was produced. Furthermore, in the observation field of 20 μm square shown by the dashed line, it was confirmed that there were no cracks exceeding 5 μm in length.

[0041] Example 2 Yb 0.3 Co4Sb 12 The thermoelectric conversion material powder was mixed with 1 mass% of MnSb powder as a sintering aid, and the mixture was compacted under a pressure of 68 MPa. The compact was then bonded to Ni foil and Ti-Al foil under a pressure of 15 MPa, in the same manner as in Example 1. Figure 9 shows the results of SEM-EDX mapping analysis of Example 2. 0.3 Co4Sb 12 It was confirmed that reaction layers consisting of Ti-Sb, Ti-Co-Sb, Ti-Al-Sb, and Co-Al with an average thickness of 20 μm or less were formed at the interface, and that no Al-Sb was formed. Furthermore, it was confirmed that there were no cracks longer than 5 μm in the observation field of 20 μm square shown by the dashed line. From the results of the semi-quantitative EDX analysis, it is believed that Ti-Sb contains known compounds such as TiSb2.

[0042] Example 3 Yb 0.3 Co4Sb 12 The thermoelectric conversion material powder was mixed with MnSb powder as a sintering aid at a ratio of 1 mass % and bonded under a pressure of 68 MPa, in the same manner as in Example 2. FIG. 10 shows the results of SEM-EDX mapping analysis of Example 3. Ti-Al foil and Yb 0.3 Co4Sb 12 It was confirmed that reaction layers consisting of Ti-Sb, Ti-Co-Sb, Ti-Al-Sb, and Co-Al with a thickness of 30 μm or less were formed at the interface between the two alloys, but no Al-Sb was formed. Furthermore, it was confirmed that there were no cracks longer than 5 μm in the observation field of 20 μm square shown by the dashed line.

[0043] Example 4 CeFe in thermoelectric conversion material powder 3.925 Mn 0.075 Sb12 The same procedure was followed as in Example 3, except that the powder was used, and the powder was held at 580° C. for 80 minutes in an Ar atmosphere and pressure sintered at 68 MPa. FIG. 11 shows the results of SEM-EDX mapping analysis of Example 4. Ti-Al foil and CeFe 3.925 Mn 0.075 Sb 12 It was confirmed that a reaction layer consisting of Ti-Sb with a thickness of 1 μm or less was formed at the interface between the two alloys, and that Al-Sb was not produced. Furthermore, it was confirmed that there were no cracks longer than 5 μm in the observation field of 20 μm square shown by the dashed line.

[0044] Example 5 When making the ingot, the molten metal is pulled out from the bottom of the crucible and solidified. The solidified ingot is subjected to the HIP process to produce a dense Ti-Al foil, and the Yb 0.3 Co4Sb 12 The same procedure was followed as in Example 1, except that the above thermoelectric conversion material powder was used. Ti-Al foil and Yb 0.3 Co4Sb 12 It was confirmed that reaction layers consisting of Ti-Sb, Ti-Co-Sb, Ti-Al-Sb, and Co-Al with a thickness of 30 μm or less were formed at the interface between the two alloys, and that Al-Sb was not produced. Furthermore, it was confirmed that there were no cracks longer than 5 μm in the observation field of 20 μm square shown by the dashed line.

[0045] The thermoelectric conversion element of Example 5 was subjected to a high-temperature storage test at 600° C. for 100 hours. The results of the SEM-EDX mapping analysis after the high-temperature storage test are shown in FIG. 0.3 Co4Sb 12 It was confirmed that reaction layers consisting of 30 μm Ti-Sb, Ti-Co-Sb, Ti-Al-Sb, and Co-Al were formed at the interface, and that no Al-Sb was generated or cracks were generated.

[0046] After the high-temperature storage test, the power generation characteristics were evaluated using a thermoelectric characteristic evaluation device (ULVAC-RIKO ZEM-3). The power factor PF (PF = S2 / ρ) was consistent within the margin of error before and after the high-temperature storage test.

[0047] Example 6 The same procedure was followed as in Example 3, except that the composition of the Ti-Al foil was Ti-34.2 mass% Al. Ti-Al foil and Yb 0.3 Co4Sb 12 A reaction layer consisting of Ti-Sb, Ti-Co-Sb, Ti-Al-Sb, and Co-Al with a thickness of 30 μm or less was formed at the interface between the two. Although a small amount of Al-Sb was generated in the reaction layer, it was confirmed that no cracks exceeding 5 μm in size were generated within an observation field of 20 μm square.

[0048] Comparative Example 1 Ti powder sieved through a sieve with a mesh size of 45 μm or less and Al powder sieved through a sieve with a mesh size of 30 μm or less were mixed in a ratio of 66 mass% Ti powder and 34 mass% Al powder, and the mixture was kept at 900° C. for 2 hours. The obtained powder was crushed to obtain a Ti-Al alloy powder. The obtained Ti-Al alloy powder and Yb 0.3 Co4Sb 12 The powders were mixed at a ratio of 35 mass% and compacted using a simple press. 0.3 Co4Sb 12 The procedure was the same as in Example 1, except that a green compact made of powder was used as the diffusion prevention layer.

[0049] Figures 13(a) and (a)' show the cross-sectional SEM observation results of the Ti-Al alloy powder 70 used. The areas enclosed by dotted lines indicate the crystal grain boundaries, and it can be seen that the interior of each Ti-Al powder particle is composed of a group of crystal grains having crystal grain boundaries with different orientation differences. As a result of the observation, the total number of individual crystal grains in the Ti-Al powder was 67, and the total area of ​​the Ti-Al powder particles from the cross-sectional observation was 0.0027 mm 2 When this was converted into a rectangular area, it would contain 67 crystal grains within an area of ​​50 μm length × 54 μm width.

[0050] Figure 13(b) shows Yb 0.3 Co4Sb 1213(c) is a cross-sectional SEM image showing a junction interface reaction layer formed between an N-type thermoelectric conversion element 22 and a diffusion prevention layer 50 by sintering a thermoelectric conversion element made of TiSb2 and Ti-Al powder. The reaction layer 501 is formed with a thickness of more than 40 μm, and it was estimated, including the result of composition analysis shown by EDX, that the reaction layer had a structure in which an Al-Sb reaction layer 503 was dispersed in a TiSb2 reaction layer 502. Furthermore, FIG. 13(c) is a cross-sectional SEM image showing a junction interface reaction layer formed by sintering a thermoelectric conversion element and Ti-Al powder when heat treatment was performed for 125 hours at a temperature of 500° C. in a reduced pressure atmosphere of 10 Pa. In the field of view of 20 μm square shown by the dashed line in the observation of FIG. 13(c), cracks were seen to have started from the generated Al-Sb reaction layer 503, and it was found that the generation of the Al-Sb reaction layer 503 causes a decrease in reliability.

[0051] The present invention has been described using examples, and the results are summarized in Table 1. The present invention is not limited to these, and the effects can be sufficiently exhibited even when various combinations are used.

[0052] [Table 1] [Explanation of symbols]

[0053] 10…Thermoelectric conversion module 21...P-type thermoelectric conversion element 22...N-type thermoelectric conversion element 30...electrode 40...Ceramic wiring board 41...First conductive member 42...Second conductive member 50...Diffusion prevention layer 501...Reaction layer 502...TiSb2 reaction layer 503...Al-Sb reaction layer 51...Metal layer 60...Joining layer 70…Ti-Al alloy powder 80…Interface

Claims

1. The method includes a step of sintering a powder of a thermoelectric conversion material containing Sb and an alloy foil containing Ti and Al in contact with each other to obtain a thermoelectric conversion material having a diffusion prevention layer, The alloy foil containing Ti and Al has a cross-sectional observation method capable of distinguishing the crystal orientation difference of 5000 μm. 2 When observing an area of ​​this size, the number of crystal grains defined by grain boundaries with a misorientation of 10 degrees or more is 1.0 or less per 5000 μm 2 and The alloy foil containing Ti and Al has an Al content of 8 mass% or more and 36 mass% or less and has a Ti 3 Al compound. A method for producing a thermoelectric conversion element comprising the steps of:

2. 2. A method for producing a thermoelectric conversion module, comprising the step of bonding a thermoelectric conversion element obtained by the method for producing a thermoelectric conversion element according to claim 1 to an electrode via the diffusion prevention layer.

Citation Information

Patent Citations

  • Semiconductor device and manufacture thereof

    JP2000252441A

  • Thermoelectric element, manufacturing method thereof, and thermoelectric module

    JP2011249442A

  • Thermoelectric conversion module and manufacturing method thereof

    JP2018160560A

  • Thermoelectric device, thermoelectric conversion module and method for manufacturing thermoelectric device

    JP2019169534A

  • Thermoelectric module and method for fabricating the same

    KR1020170076358A